ULASAN Masalah Pencoklatan pada Kultur Jaringan - Sri Hutami (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2008)
Severaltropical plant species contain high concentrations of phenoliccompounds, which become oxidised when their cellsare wounded or when the plant parts become senescences.In tissue culture, the phenolic compounds usually leach intothe medium from the cut surfaces of explants. The phenoliccompounds caused the culture medium turns to dark brownin colour due to oxidation. This is detrimental to the culture,because it causes the isolated tissue fails to grow. Thebrowning of tissue culture and the medium can often beprevented by one of the several different approaches, suchas by removing the phenolic compounds produced, modifyingthe redox potential, inactivating phenolase enzymes,reducing phenolase activity and substrate availability, as wellas pre-treatments by soaking and preconditioning on a basalmedium.